Principles and methods of social research - Crano, William D., 1942-; Brewer, Marilynn B., 1942-; Lac, Andrew (New York : Routledge, 2015)
"This classic text presents the most recent advances in social research design and methodology. Users applaud the book's comprehensiveness. It reviews experimental, correlational, quasi experimental, and evalaution designs to survey sampling, interviewing, content analysis, questionaire design, scale developments, and assessing dyads and groups. The research process is described using basic principles of scientific inquiry and how they apply to the study of human behavior. Design issues are emphasized over statistical computations. The book helps readers apply sound scientific analysis to better understand what it means to be human, making it an indispensable resource in the fields of psychology, communication, sociology, education, health, and marketing. With a heavy emphasis on reliability, validity, and measurement, the book considers experimental, quasi-experimental, and survey research designs in light of these qualities. Principles and Methods of Social Research is noted for its: -Emphasis on understanding the principles that govern the use of a method to facilitate the researcher's choice of the best technique for a given situation. - Use of the laboratory experiment to describe and evaluate field experiments, correlational designs, quasi experiments, evaluation studies, and survey designs. Coverage of the ethics of social research including the power a researcher wields and tips on how to use it responsibly. "--
Includes bibliographical references and index.
Keywords: Social sciences -- Research; Social sciences -- Methodology; PSYCHOLOGY / Research & Methodology; SOCIAL SCIENCE / Methodology; SOCIAL SCIENCE / Research